Applicability of randomized trials in radiation oncology to standard clinical practice. Issue 16 (14th May 2013) - Apisarnthanarax, Smith; Swisher‐McClure, Samuel; Chiu, Wing K.; Kimple, Randall J.; Harris, Stephen L.; Morris, David E.; Tepper, Joel E.
<x xml:space="preserve">Abstract</x> BACKGROUND Randomized controlled trials (RCTs) are commonly used to inform clinical practice; however, it is unclear how generalizable RCT data are to patients in routine clinical practice. The authors of this report assessed the availability and applicability of randomized evidence guiding medical decisions in a cohort of patients who were evaluated for consideration of definitive management in a radiation oncology clinic. METHODS The medical records of consecutive, new patient consultations between January and March 2007 were reviewed. Patient medical decisions were classified as those with (Group 1) or without (Group 2) available, relevant level I evidence (phase 3 RCT) supporting recommended treatments. Group 1 medical decisions were further divided into 3 groups based on the extent of fulfilling eligibility criteria for each RCT: Group 1A included decisions that fulfilled all eligibility criteria; Group 1B, decisions that did not fulfill at least 1 minor eligibility criteria; or Group 1C, decisions that did not fulfill at least 1 major eligibility criteria. Patient and clinical characteristics were tested for correlations with the availability of evidence. RESULTS Of the 393 evaluable patients, malignancies of the breast (30%), head and neck (18%), and genitourinary system (14%) were the most common presenting primary disease sites. Forty‐seven percent of all medical decisions (n = 451) were made without available (36%) or applicable (11%) randomized evidence to inform clinical decision making. Primary tumor diagnosis was significantly associated with the availability of evidence (P < .0001). CONCLUSIONS A significant proportion of medical decisions in an academic radiation oncology clinic were made without available or applicable level I evidence, underscoring the limitations of relying solely on RCTs for the development of evidence‐based health care. Cancer 2013;119:3092—3099. © 2013 American Cancer Society.